Angular momenta in fields from a rotational mechanical antenna‡JPCO-102088.R3, Submitted to J. Phys. D: Appl. Phys. on 13th May, transferred to J. Phys. Commun. 3rd August, revised 17th Nov. and 5th Dec., accepted 8th Dec. 2021. (24th December 2021) - Mao, Yu; Liu, Y; Lin, Hai
Abstract: Mechanic antennas provide opportunities for human portable, VLF communications, where a rotational dipole emits EM signals with angular momenta. In this paper we analytically derive the electromagnetic fields from a rotational electric dipole using Fourier transform method, and find that the radiated fields from the rotational electric dipole carries nonzero energy flow density in both orbital and spin angular momentum (AM) parts by their flux tensors. Intuitively, a dipole circulating on the transverse plane induces a longitudinal orbital angular momentum and a longitudinal spin angular momentum. And the binding force for the rotational electric dipole is then shown to result mainly from the Coulomb fields. We believe that our work will contributes to novel communication designs for portable mechanic antennas.